The Impact of Free Fire Online Games on Students' Social Behavior at Elementary School - Dian Febriady; Putri Hana Pebriana; Melvi Lesmana Alim; Rizki Ananda (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to determine the impact of the online game Free Fire on students' social behavior at SDN 004 Bangkinang Kota. This research is quantitative research using the exposed facto method. The population in this study were third-grade students at SD Negeri 004 Bangkinang Kota, while the sample used in this study consisted of 40 students. The essential findings obtained were that students at SD Negeri 004 Bangkinang Kota were addicted to online games, which had an impact on the social behavior of students who tended to get angry quickly and use harsh or impolite language with teachers and friends. Online game addiction experienced in childhood can affect aspects of students' social behavior in living their daily lives, especially in class III students of SD Negeri 004 Bangkinang Kota, who are entering their final childhood. Hence, discussing the positive and negative impacts in more detail is necessary. Carry on. Online games can have a positive effect. Students can practice mindsets, socialize with fellow teams, and act as entertainers when tired. Online games can also have a negative impact because they can affect student behavior patterns, interfere with health, and cause addiction. The results showed that 26 respondents (65%) had the intensity of playing free fire online games in the frequent category. As much as 45% of free fire online gameplay has a positive impact on students, and as much as 55% of free fire online gameplay harms students. The study results show the effect of the online game Free Fire on the social behavior of students at SD Negeri 004 Bangkinang Kota.